Performance evaluation and crossbreeding effects for body weight and conformation traits in different breeds of ducks - PADHI, M K; SAHOO, S K (The Indian Journal of Animal Sciences, 2012)
A 3×3 full diallel experiment was carried out using 3 breeds of ducks, viz. Indigenous duck (D), Khaki Campbell (C) and White Pekin (P), to evaluate the juvenile body weights and conformation traits and to estimates different crossbreeding genetic parameters in 609 ducklings from nine genetic groups. Significant differences between different genetic groups were observed for all the traits measured. Direct genetic effects, maternal effects and heterosis were significant for all the traits studied. Heterosis was in desirable direction for all the traits. Overall results revealed that crossbreds performed significantly higher than the purebreds. C × P recorded highest body weight amongst the crossbreds at 8 weeks of age. Heterosis (%) estimates for 8 week body weight, shank length and keel length were positive. Since both additive and non-additive genetic effects are important for the juvenile traits, establishment of pure lines with specialized sire and dam lines followed by crossing is ideal for the production of different crosses for the commercial duck farming.